PENGARUH NISBAH BAGI HASIL, PRODUK DOMESTIK BRUTO, SUKU BUNGA DEPOSITO DAN INFLASI TERHADAP SIMPANAN MUDHARABAH DI PERBANKAN SYARIAH INDONESIA PERIODE 2004.12009.2 - nurjanah nurjanah; Sumiyarti Sumiyarti (Media Ekonomi, 2010)
This study focused on examination impact of Profit Sharing Ratio (NSM) to Mudharabahsavings in Indonesia Syariah Bank. The model used in this study is the Multiple LinearRegression OLS methods (Ordinary Least Square) with the time series data in period2004.1-2009.2. But in this model, we also considerd Gross Domestic Product (PDB), DepositInterest Rate (RSK), and Inflation (INF) as control variables. The results of the researchare variables of Profit Sharing Ratio (NSM), Deposit Interest Rate (RSK) and Inflation(INF) are affected not statistically affected Mudharabah Savings. The other side, thevariable of Gross Domestic Product (GDP) statistically affects Mudharabah Savings. Theinterest of people on Mudharabah Savings is not because of the Profit Sharing Ratio thatbecome the main determinant in Mudharabah Saving but of the more Islamic System.